LEXICAL STYLISTIC DEVICES ("Conference on Universal Science Research 2023", 2023)
The level of study and meaning of lexical literary devices are presented in the given article. Essential aspects of lexical tools and information about various research methods and their study will be discussed. Terms belonging to the lexical level of the language and analyzes of lexical devices given by a number of terminological dictionaries and literary sources will be explained in the article. In this article, we would like to mention different approaches to the study of literary terminology of figurative language, more specifically lexical stylistic devices. There are many types of figurative language, including literary devices such as similes, metaphors, personification, and many others.